Microbiological properties and molecular profiling of microbial ecosystems during spontaneous fermentation of Garcinia mangostana pericarps: article - Hisham, Aishahtulbadariah; So’aib, Mohamad Sufian (2017)
Spontaneous fermentation is a process that can improve the quality of foods characteristics. In this research, the fermentation undergoes naturally with no starter culture added. The microflora present in the raw materials eventually result the unknown microorganisms present during fermentation. This research is to study the microbiological properties that present during fermentation. Garcinia mangostana pericarps are used as the raw materials for spontaneous fermentation. The phenotyping characterization was conducted by biochemical characteristics which is Gram staining and catalase production. The microbial community is further investigated by molecular profiling method which is by PCR amplification and sequencing. During fermentation, species of Bacillus namely, Bacillus sp., Bacillus cereus and Mycobacterium sp. are present. From Lactobacillus, the species are Lactobacillus plantarum and Lactobacillus brevis. There were also other bacteria species such as Klebsiella spp. and Enterobacteriaceae spp.